'Development and psychometric evaluation of the safety feeling scale in adult patients at hospital: Exploratory sequential mixed method' - Sahar Dabaghi; Mitra Zandi; Abbas Ebadi; Abbas Abbaszadeh; Camelia Rohani (Wiley, 2023)
Abstract Aim and Objectives This study aimed to develop and examine psychometric properties of the safety feeling scale (SFS) in adult patients to assess their sense of safety during a hospital stay. Design Mixed methods design. A SQUIRE checklist was used. Methods This is a study with two phases of scale development and evaluation of the psychometric properties of the scale. In the first phase, the concept of 'safety feeling' was analysed using a hybrid model. Thus, a systematic review and then a qualitative study with hospitalized patients (n = 31) were conducted by conventional content analysis. In the psychometric phase, factorial validity, reliability, feasibility, and responsiveness of the scale were evaluated by different tests in various samples. Results After integrating the results of the systematic review and qualitative study, a scale item pool with 84 items was developed. In the psychometric phase, 12 items with four factors were specified; 'effective care,' 'confidence in the healthcare team,' 'emotional enrichment' and 'hygienic facilities,' explaining 51% of the total variance of the scale. They were confirmed by confirmatory factor analysis. Internal consistency and stability of the scale were satisfactory. Feasibility and responsiveness were also acceptable.